2016
DOI: 10.1080/1034912x.2016.1174191
|View full text |Cite
|
Sign up to set email alerts
|

Does Empathy Predict Instructional Assignment-Related Stress? A Study in Special and General Education Teachers

Abstract: The role of empathy in the teaching profession has been vastly investigated in relation to its effect on students, but research on how teachers' empathy affects their own well-being at work is limited. This study investigated empathy and instructional assignmentrelated stress factors of primary school teachers serving in general or special education; moreover, it investigated if empathy predicted instructional assignment-related stress. Data were collected from 190 primary school teachers using the Interperson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Professional development with an emphasis on curriculum, school administration or human resources has long been the focus of attention within education (Wessels & Wood, 2019). Prominent within existing literature is the significance of deliberately fostering and enhancing the capacity of SE teachers and accompanying systems to effectively identify and acknowledge distinct emotional intricacies inherent in their profession (Olagunju et al, 2021;Platsidou & Agaliotis, 2017;Rae et al, 2017;Womack & Monteiro, 2023;Xu et al, 2023). Rae et al (2017) proposed educating SE teachers on emotional literacy, with the goal of fostering successful teacher-pupil relationships in all areas of learning.…”
Section: Professional Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Professional development with an emphasis on curriculum, school administration or human resources has long been the focus of attention within education (Wessels & Wood, 2019). Prominent within existing literature is the significance of deliberately fostering and enhancing the capacity of SE teachers and accompanying systems to effectively identify and acknowledge distinct emotional intricacies inherent in their profession (Olagunju et al, 2021;Platsidou & Agaliotis, 2017;Rae et al, 2017;Womack & Monteiro, 2023;Xu et al, 2023). Rae et al (2017) proposed educating SE teachers on emotional literacy, with the goal of fostering successful teacher-pupil relationships in all areas of learning.…”
Section: Professional Developmentmentioning
confidence: 99%
“…Stress is a natural response to job demands such as workload and time pressures (Brunsting et al, 2014;Cancio et al, 2018;Platsidou & Agaliotis, 2008), whereas burnout has been described as the result of chronic stress, resulting in a state of physical and emotional exhaustion (Carroll et al, 2022;McDowell, 2017;Riley, 2014). There is a distinction in the literature between teacher stress, burnout and wellbeing where teacher wellbeing is conceptualised not as an absence of stress but rather the creation of an environment supportive of teachers' emotional and physical needs (Cancio et al, 2018;Hester et al, 2020;Kaynak, 2020;Kim & Lim, 2016;Platsidou & Agaliotis, 2017;Wessels & Wood, 2019). There has been much focus on SE teacher burnout and stress within educational research and how to best mitigate these factors to boost wellbeing (Brunsting et al, 2014;Cancio et al, 2018;Herman et al, 2023;Hester et al, 2020;Kiel et al, 2016), further perpetuating the myth of wellbeing as an absence of stress and burnout.…”
mentioning
confidence: 99%
“…The few studies involving teachers showed that high levels of empathy were associated with stress in both mainstream and special school teachers [18] and that the affective aspect of empathy in particular was a predictor of teacher stress [19]. Teachers dealing with students with special educational needs are at risk of developing empathy fatigue [16], especially when dealing with students with mental health problems [20].…”
Section: Introductionmentioning
confidence: 99%